2021
DOI: 10.1002/adsc.202100275
|View full text |Cite
|
Sign up to set email alerts
|

Relay Cu(I)/Brønsted Base Catalysis for Phospha‐Michael Addition/5‐exodig Cyclization/Isomerization of insitu Formed aza‐Alkynyl o‐quinone methides with P(O)−H compounds to C3‐Phosphorylated Indoles

Abstract: A relay Cu(I)/Brønsted base catalyzed one‐pot phospha‐Michael addition/5‐exo‐dig cyclization/isomerization of in situ generated aza‐alkynyl o‐quinone methides (N‐o‐AQMs) from 1‐(o‐aminophenyl)prop‐2‐ynols with P(O)‐compounds has been established to afford C3‐phosphorylated indoles. It demonstrates that the 1,4‐conjugate addition adduct from N‐o‐AQMs could undergo further cyclization with the tethered alkyne moiety to afford N‐heterocyclic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 107 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Based on our previous experience of the activation of a C–OH bond using a Lewis or a Brønsted acid, 12 we commenced our study by investigating some metal Lewis acids in the model reaction of the 2 H -chromene hemiketal 1a with phenylacetylene 2a in ClCH 2 CH 2 Cl at 90 °C (Table 1). Unfortunately, the use of 10 mol% of Bi III -, 12 f Sc III -, Y III -, 9 i Ga III - and Fe III - 10 b , c derived metal triflates and Fe(ClO 4 ) 3 · x H 2 O resulted in no reaction (entries 1–6).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous experience of the activation of a C–OH bond using a Lewis or a Brønsted acid, 12 we commenced our study by investigating some metal Lewis acids in the model reaction of the 2 H -chromene hemiketal 1a with phenylacetylene 2a in ClCH 2 CH 2 Cl at 90 °C (Table 1). Unfortunately, the use of 10 mol% of Bi III -, 12 f Sc III -, Y III -, 9 i Ga III - and Fe III - 10 b , c derived metal triflates and Fe(ClO 4 ) 3 · x H 2 O resulted in no reaction (entries 1–6).…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated that the products 429 obtained through the developed strategy can be used as intermediates for the synthesis of functionalized indoles. 214 Several metal-catalyzed oxidative couplings to construct C− P bonds have been developed for the synthesis of N-containing heterocyclic phosphonates. Substituted 2-and 3-phosphoindoles 432 can be afforded in moderate to good yields using Ag 2 CO 3 /Mg(NO 2 ) 2 and diphenylphosphine oxide or dialkyl phosphites (431) in acetonitrile (Scheme 86, eq 1).…”
Section: Five-membered Rings: Nonaromatic Aromatic and Benzo-fused He...mentioning
confidence: 99%
“…This protocol needs the presence of a Brønsted base such as Et 3 N and CuBF 4 (CH 3 CN) 4 as catalyst, and proceeds by a sequence that implies a phospha-Michael addition, followed by a 5-exo-dig cyclization and an isomerization of aza-alkynyl o -quinone methides, which were formed in situ (Scheme ). The authors demonstrated that the products 429 obtained through the developed strategy can be used as intermediates for the synthesis of functionalized indoles …”
Section: Five-membered Rings: Nonaromatic Aromatic and Benzo-fused He...mentioning
confidence: 99%
“…Among them, the phosphorylation of alcohols with H-phosphine oxides has been successfully developed for the construction of C–P bonds since 2000 (Scheme , path C) . Subsequently, metal salts including Cu­(OTf) 2 , Pd­(acac) 2 , CdCl 2 , AgOTf, and Bi­(OTf) 3 exhibited excellent catalytic activities for the phosphorylation of allylic alcohols, propargylic alcohols, and tertiary aromatic alcohols. In 2017, Xie and Loh found the first example of C–P bond formation via a dehydrative cross-coupling reaction of C–OH/P–H from MBH (Morita–Baylis–Hillman) alcohols and phosphine oxides with high Z selectivity in the absence of catalysts, additives, and solvents . And they also achieved the dehydrative allylation of P–H species with allylic alcohols catalyzed by the strong Lewis acid B­(C 6 F 5 ) 3 .…”
Section: Introductionmentioning
confidence: 99%